Development of students' worksheet-based AR video and QR-timer test on biographical text materials Class X Senior High School 1 Pelalawan - Darmawan, Tengku Hamid; Charlina, Charlina; Septyanti, Elvrin (Universitas Negeri Yogyakarta, 2024)
Student worksheets are learning tools in the form of direct assignments to simplify the evaluation process. Unfortunately, the use of student worksheets is still conventionally based and burdensome for students. The proposed innovation is the development of a student worksheet integrated with QR Code digital technology, containing AR Video, and also G-Form links with material of National Biographical Indonesian Hero which is given an automatic countdown timer test extension. This research aims to determine the increase in students' interest in learning and understanding the material after using student worksheets, provide an overview of optimizing digital content and assignments for teachers and students, as well as develop the form and function of student worksheets in a more complex manner by involving digital media in the form of AR Video and QR Code integrated Form Timer Exercises. The research model uses a 4D model (define, design, develop, and disseminate). The test subjects were 25 class X students at Senior High School 1 Pelalawan. Data sources were obtained from interviews, questionnaires for needs analysis, and results questionnaires. The data in this research were analyzed using qualitative descriptive techniques to analyze interview information and quantitative analysis techniques to process data in questionnaires for needs analysis and result questionnaires. This research had received very appropriate criteria in validating research products (90%) and received very positive perceptions from class X students at Senior High School 1 Pelalawan (88%). These exact results are expected to be developed and studied further, especially related to the relationship of this media with an increase in student learning outcomes.